Leadership as a Critical Success Factor for Small and Medium Enterprises’ Quality Management. Reflections for Discussion - Santamaría-Peraza, Roselin (2020)
DOI: https://doi.org/10.26439/ing.ind2020.n038.4815 The objective of this study is to establish the variables that determine leadership as a critical factor for quality management success. The research was conducted as a documentary analysis with a descriptive approach. The main finding of the research was the importance of leadership to carry out processes related to its quality and improvement. Moreover, it is concluded that the most prominent skills of leaders are their ability to influence others to act, their ability to be followed, and their willingness to achieve results.